A transcription factor for cold sensation! - Milbrandt Jeffrey; Qu Zhican; Kim Susan J; Zhuo Min (SAGE Publishing, 2005)
Abstract The ability to feel hot and cold is critical for animals and human beings to survive in the natural environment. Unlike other sensations, the physiology of cold sensation is mostly unknown. In the present study, we use genetically modified mice that do not express nerve growth factor-inducible B (NGFIB) to investigate the possible role of NGFIB in cold sensation. We found that genetic deletion of NGFIB selectively affected behavioral responses to cold stimuli while behavioral responses to noxious heat or mechanical stimuli were normal. Furthermore, behavioral responses remained reduced or blocked in NGFIB knockout mice even after repetitive application of cold stimuli. Our results provide strong evidence that the first transcription factor NGFIB determines the ability of animals to respond to cold stimulation.